1999
DOI: 10.1515/jpem.1999.12.2.153
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Treatment with Recombinant Human Growth Hormone of Children with Meningomyelocele and Growth Hormone Deficiency: A Comparison of Supine Length and Arm Span

Abstract: Growth retardation and precocious puberty are frequently found in children with meningomyelocele (MMC). Lower limb contractions, spasticity and kyphoscoliosis may lead to disproportionate short stature. Most of these patients have structural brain defects or hydrocephalus which can cause growth hormone deficiency. In this study, 19 children aged between 3.5 and 12.8 years with MMC and growth hormone (GH) deficiency were treated with recombinant human GH for a period of 12 months. Supine length, arm span and gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 20 publications
(7 reference statements)
2
13
0
Order By: Relevance
“…Our data would support previously published reports (13)(14)(15)(16)(17)(18)(19) that arm span is a better parameter than height to calculate body functions for patients with myelomeningocele and scoliosis and/or hypoplastic lower extremities. For patients with myelomeningocele and with intermediate or minimal paralysis (LL2 and LL3) without scoliosis or lower extremity hypoplasia, either height or arm span can be reliably used to estimate BMI.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our data would support previously published reports (13)(14)(15)(16)(17)(18)(19) that arm span is a better parameter than height to calculate body functions for patients with myelomeningocele and scoliosis and/or hypoplastic lower extremities. For patients with myelomeningocele and with intermediate or minimal paralysis (LL2 and LL3) without scoliosis or lower extremity hypoplasia, either height or arm span can be reliably used to estimate BMI.…”
Section: Discussionsupporting
confidence: 90%
“…The arm span as a substitute for height method we propose is applicable to most clinics caring for patients in wheelchairs or for those where it is difficult to obtain height or linear length measures because of the patients' inability to stand, their scoliosis, or their lower extremity deformities (13)(14)(15)(16)(17)(18)(19). We have not used more stringent investigative measures (4-9,11) in our study because they are expensive or radioactive and not available in most clinic situations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity rates among people with spina bifida have been assessed by a variety of methods [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] and range from 28 to 50% among children to 34-64% among adolescents and adults [9,16,17,23,24]. The causes of obesity in this population are multifactorial.…”
Section: Introductionmentioning
confidence: 99%
“…In 1989, Rotenstein et al [10] first reported on a positive short-term GH response in seven pre-pubertal MMC patients. However, there are still only few reports available documenting short-term treatment effects of hGH [11][12][13][14]. Since these first published reports, there is an ongoing discussion concerning long-term efficacy and safety.…”
Section: Introductionmentioning
confidence: 99%